2018
DOI: 10.1089/jwh.2017.6364
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Duration of Reproductive Years and Metabolic Syndrome

Abstract: Longer reproductive years were significantly associated with a decreased prevalence of MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The associations between abdominal adipose tissue and brain characteristics are consistent with previous studies linking elevated adipose tissue to older brain age (Beck et al, 2022;Subramaniapillai et al, 2022), lower brain volume (Cho et al, 2021;Debette & Markus, 2010;Gurholt et al, 2021;Isaac et al, 2011;Veit et al, 2014), and higher WMH load (Arnoldussen et al, 2019;Lampe et al, 2019;Park et al, 2018;Vuorinen et al, 2014). The relationships were strongest for WMH volume, suggesting that brain white matter may be particularly sensitive to elevated abdominal adipose tissue in post-menopausal females.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The associations between abdominal adipose tissue and brain characteristics are consistent with previous studies linking elevated adipose tissue to older brain age (Beck et al, 2022;Subramaniapillai et al, 2022), lower brain volume (Cho et al, 2021;Debette & Markus, 2010;Gurholt et al, 2021;Isaac et al, 2011;Veit et al, 2014), and higher WMH load (Arnoldussen et al, 2019;Lampe et al, 2019;Park et al, 2018;Vuorinen et al, 2014). The relationships were strongest for WMH volume, suggesting that brain white matter may be particularly sensitive to elevated abdominal adipose tissue in post-menopausal females.…”
Section: Discussionsupporting
confidence: 88%
“…The relationships between oestrogen exposure, body composition, and brain health in females are complex and largely unexplored. The menopause transition is linked to an accelerated increase of central fat accumulation (Lizcano & Guzmán, 2014), and abdominal adipose tissue has been associated with higher grey matter (GM) and white matter (WM) brain age (Beck et al, 2022(Beck et al, , 2021bSubramaniapillai et al, 2022), WM hyperintensities (WMH) (Arnoldussen et al, 2019;Han et al, 2021;Lampe et al, 2019;Pasha et al, 2017;Park et al, 2018;Vuorinen et al, 2014), and dementia risk (Kiliaan et al, 2014;Tang et al, 2021;Razay et al, 2006;Whitmer et al, 2008). However, in females, adipose tissue also serves as the primary biosynthesis site of oestrogens post-menopause (Steiner & Berry, 2022;Bhardwaj et al, 2019;Kershaw & Flier, 2004;Siiteri, 1987;Simpson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in menopausal women, lipoprotein lipase activity was reported to increase in both the abdominal and the gluteal regions, inducing fat accumulation in the form of intramuscular fat [30][31][32]. This might lead to a higher risk for metabolic syndrome in postmenopausal women with a short duration of reproductive span [33]. Recently, Shin and Kwon reported that a short reproductive span had a causal relationship with increased risk of insulin resistance [34].…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence of the protective effect of estrogen was provided in an animal model, in which 17 β-estradiol administered parenterally to ovariectomized monkeys resulted in 50-70% decreases in coronary artery atherosclerosis [35]. The mechanism underlying the protective effects of estrogen on vessels has been reported to involve fibroblast growth factor-2, vascular endothelial growth factor, and nitric oxide synthesis [36][37][38], and recently, reproductive span was demonstrated to be inversely related to cardiovascular disease [39] and metabolic syndrome [33]. We cautiously suggest that these findings and our finding that reproductive span is significantly and inversely association with sarcopenia indicate that a lack of estrogen and systemic and vessel inflammation underlie these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Too short or too long, a childbearing period can increase a woman's risk of developing diabetes. Studies have also shown that the long childbearing period was a simple positive correlation with the risk of diabetes ( 9 , 14 ).…”
Section: Introductionmentioning
confidence: 99%